Default mode network and visual network responsiveness to transcutaneous auricular vagus nerve stimulation predict its variable efficacy in primary insomnia disorder - Wu, Xiao; Duan, Hua; Wang, Yishuang; She, Shuya; Hu, Yushi; He, Benxiang (Frontiers in Neurology, 2025)
BackgroundsTranscutaneous auricular vagus nerve stimulation (taVNS) has been proven effective in treating primary insomnia disorder (PID). However, its efficacy exhibits inter-individual variability.ObjectivesThis study aimed to investigate the brain functional mechanisms underlying variable efficacy and to identify potential biomarkers that could predict taVNS efficacy.MethodsWe conducted a randomized controlled trial involving 54 PID patients who received real or sham taVNS to assess brain activity and autonomic nervous system (ANS) responses. An additional 46 patients receiving real taVNS were recruited to enlarge the treatment cohort, thereby enhancing the statistical power for biomarker identification.ResultsPost-treatment, the mean amplitude of low-frequency fluctuations (mALFF) of sensorimotor network (SMN), default mode network (DMN), and visual network (VN) in treatment group were significantly increased than those before treatment, and the mALFFs value of the combination of all the differentially significant brain regions (especially DMN + VN) before taVNS were correlated with its efficacy. The heart rate variability indicators “root mean square of successive differences, percentage of adjacent N-N intervals differing by more than 50 ms, and high frequency (HF) during taVNS were significantly greater than pre-treatment. The mALFFs value of DMN and VN before taVNS were correlated with HF during taVNS.ConclusionOur findings suggest that taVNS may exerts therapeutic effects in PID through modulating the activities of the DMN (left precuneus and bilateral cuneus), VN (left lingual gyrus, left superior occipital gyrus, left cuneus and bilateral calcarine), and SMN (right precentral, right rolandic operculum, bilateral postcentral gyrus, bilateral paracentral gyrus, bilateral supplementary motor areas and left middle cingulate gyrus), thereby regulating the ANS activity in PID patients. Individual differences in functional responsiveness of the DMN + VN + SMN networks, particularly “DMN (left Precuneus and left cuneus) + VN (left superior occipital and left cuneus)” to ANS modulation during taVNS were correlated with variability in efficacy. Additionally, baseline DMN/VN activity and HF parameters during stimulation demonstrated potential as predictive biomarkers for taVNS efficacy.Clinical trial registrationThis study protocol was registered with the Chinese Clinical Trial Registry (Registration Number: ChiCTR2300076474; accessible at www.chictr.org.cn).